Abstract PSSE 2007 Braumann - Braumann, Carlos A. (2008)
Scientific meeting: International Conference Probability and Statistics in Science and Technology, a Bernoulli Society Satellite Meeting of ISI’2007, Porto, Portugal, Aug 30-Sep 1, 2007. Oral communication on stochastic differential equation models for population growth in a random environment with density-dependent noise intensities.